Follicular epithelium, theca and egg envelope formation in Serrasalmus spilopleura (Teleostei, Characiformes, Characidae) - Quagio-Grassiotto, I; Guimaraes, ACD (Blackwell Publishing, 2003)
The follicular epithelium and theca of oocytes in Serrasalmus spilopleura differentiates during the initial primary growth phase. The follicular cells are squamous and the thecal cells are disposed in two layers. During the secondary growth phase, follicular cells become cuboidal, acquire characteristics typical of protein- or glycoprotein-producing cells, and show dilated intercellular spaces. Formation of the egg envelope in S. spilopleura begins in the previtellogenic oocytes as a layer of amorphous electron-dense material is laid down on the oolemma. During vitellogenesis, another layer of electron-dense material appears beneath the first layer. Also during this phase, a layer of amorphous, less electron-dense material is formed adjacent to the follicular epithelium. The secondary egg envelope appears at the postvitellogenic phase and is composed of a filamentous and undulant material. The morphology of the egg envelopes in S. spilopleura reflects not only its oviparous nature but also the fact that its eggs are adhesive.
Keywords: fallicular epithelium; theca and egg envelope